MR neurography: diagnostic imaging in the PNS - Hayes, Jennifer; Bendszus, Martin; Pham, Mirko (Clinical neuroradiology, 2015)
The diagnostic work-up of peripheral neuropathies is often challenging and is mainly based on a combination of clinical and electrophysiological examinations. One of the most important difficulties is the accurate determination of the lesion site (lesion localization), lesion extension, and spatial lesion dispersion, which all represent essential diagnostic information crucial for finding the correct diagnosis and hence an adequate therapeutic approach. A typical pitfall in the conventional diagnostic reasoning is the differentiation between a distal, complete cross-sectional nerve lesion and a more proximally located, fascicular nerve lesion. Magnetic resonance neurography (MRN) has been proven to be capable of improving the diagnostic accuracy by providing direct, noninvasive visualization of nerve injury with high structural resolution even reaching the anatomical level of single nerve fascicles (fascicular imaging) and at the same time with large anatomical coverage. It is also feasible to detect structural nerve damage earlier and with higher sensitivity than gold-standard nerve conduction studies. The purpose of this study is to review the literature for current developments and advances in MRN for the precise spatial detection of nerve lesions in focal and non-focal disorders of the peripheral nervous system.
Gesehen am 15.07.2020